Can a single lower trunk body-fixed sensor differentiate between level-walking and stair descent and ascent in older adults? Preliminary findings. Issue 10 (October 2016) - Weiss, Aner; Brozgol, Marina; Giladi, Nir; Hausdorff, Jeffrey M.
Highlights: Stair negotiation and level-walking were evaluated using a single body-fixed sensor. Stair negotiation and level-walking can be characterized by distinct features. These findings provide a first step towards activity recognition in daily living. Abstract: Stair ascent and descent are common forms of ambulation that may be challenging to detect. Here, we propose the first step towards differentiating between stair negotiation and level-walking using a single body-fixed sensor. Seventeen healthy older adults (age: 79.3 ± 4.2 years, 47% women) wore a body-fixed sensor on the lower-back while performing level-walking and stair negotiation. Measures derived from the 3D acceleration and angular-velocity signals included medians, ranges, step duration, step and stride regularity, filtered vertical to horizontal acceleration ratio (VAF/HAF), and wavelet-based features. Friedman's and Wilcoxon tests compared between conditions. Stepwise-binary logistic-regression evaluated classification accuracy. During level-walking, yaw range was lowest and anterior–posterior and vertical step and stride regularity were highest ( p ≤ 0.007). Anterior–posterior step regularity ( p = 0.003), VAF/HAF ( p = 0.094), and yaw range ( p = 0.105) identified level-walking (92.2% accuracy). During stair ascent, roll range, median anterior–posterior acceleration and anterior–posterior wavelet-coefficient were lowest ( p ≤ 0.006), while VAF/HAF was highest ( p = 0.0029). Anterior posterior wavelet coefficient ( p = 0.038) and VAF/HAF ( p = 0.018) identified stair ascent (94.3% accuracy). During stair descent, vertical and medio-lateral ranges were highest and medio-lateral stride regularity and VAF/HAF were lowest ( p ≤ 0.006). VAF/HAF ( p = 0.01), medio-lateral acceleration range ( p = 0.069), and medio-lateral stride regularity ( p = 0.072) identified stair descent (90.2% accuracy). These findings suggest that a single worn body-fixed sensor can be used to differentiate between level-walking and stair negotiation.